2021
DOI: 10.1108/jsbed-08-2020-0306
|View full text |Cite
|
Sign up to set email alerts
|

Social support as a driver of social entrepreneurial intentions: the moderating roles of entrepreneurial education and proximity to the US small business administration

Abstract: PurposeThe purpose of this paper is two-fold: to examine the relationship between social support and social entrepreneurial intentions and to test the moderating roles of entrepreneurial education and physical proximity to the office of the US Small Business Administration.Design/methodology/approachThe study adopts a quantitative methodological approach. The hypotheses are tested on a sample of 1,245 respondents who intend to start a business in the state of Florida. Factor analysis and multiple regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 99 publications
5
21
0
1
Order By: Relevance
“…In addition, the statistical analysis revealed that social safeness moderates or strengthens the relationship between HFU and life satisfaction. This finding is consistent with findings from other international studies (Shah, Amjed, & Jaboob, 2020; Seyoum, Chinta, & Mujtaba, 2021) that have determined the moderating effect of the social safeness variable in various contexts. There is a lack of research on the moderating effect of social safeness on the relationship between HFU and life satisfaction.…”
Section: Methodological Aspectssupporting
confidence: 92%
“…In addition, the statistical analysis revealed that social safeness moderates or strengthens the relationship between HFU and life satisfaction. This finding is consistent with findings from other international studies (Shah, Amjed, & Jaboob, 2020; Seyoum, Chinta, & Mujtaba, 2021) that have determined the moderating effect of the social safeness variable in various contexts. There is a lack of research on the moderating effect of social safeness on the relationship between HFU and life satisfaction.…”
Section: Methodological Aspectssupporting
confidence: 92%
“…Entrepreneurship education's goals must be considered while designing an evaluation study. It is vital to note that entrepreneurship education is distinct from education about entrepreneurship (Seyoum et al 2021;Tang et al 2022). Entrepreneurship education aims to increase students' understanding of the many facets of starting and operating a firm.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…A growing literature also identifies individual's creativity and prosocial motivation as important antecedents of social entrepreneurial intentions (Yu et al, 2020). However, in a recent study, found a positive and significant relation between social support and social entrepreneurial intentions (Seyoum, Chinta and Mujtaba, 2021).…”
Section: Opportunity In Actionmentioning
confidence: 96%